If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 280 = (18 + -1x) * x + 20x Reorder the terms for easier multiplication: 280 = x(18 + -1x) + 20x 280 = (18 * x + -1x * x) + 20x 280 = (18x + -1x2) + 20x Reorder the terms: 280 = 18x + 20x + -1x2 Combine like terms: 18x + 20x = 38x 280 = 38x + -1x2 Solving 280 = 38x + -1x2 Solving for variable 'x'. Reorder the terms: 280 + -38x + x2 = 38x + -38x + -1x2 + x2 Combine like terms: 38x + -38x = 0 280 + -38x + x2 = 0 + -1x2 + x2 280 + -38x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 280 + -38x + x2 = 0 Factor a trinomial. (10 + -1x)(28 + -1x) = 0Subproblem 1
Set the factor '(10 + -1x)' equal to zero and attempt to solve: Simplifying 10 + -1x = 0 Solving 10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10Subproblem 2
Set the factor '(28 + -1x)' equal to zero and attempt to solve: Simplifying 28 + -1x = 0 Solving 28 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -1x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -1x = 0 + -28 -1x = 0 + -28 Combine like terms: 0 + -28 = -28 -1x = -28 Divide each side by '-1'. x = 28 Simplifying x = 28Solution
x = {10, 28}
| 104=38-3x | | x+50+10+x=180 | | (15x-23)+(8x+12)=180 | | 65+195(x-1)=2405 | | 0.35*x+1.6=-0.5 | | -71+5x=48-2x | | 4x+12=5x+9-x+3 | | -71+5c=48-2x | | 65+195x= | | (2x+7)+32=5x-15 | | -4=-1-4 | | 2a+3b+3c=74 | | 12x-153=2x+77 | | 11(y+4)=66 | | 9x^2-6x+1=18x^2-2 | | 18-(6-10y)=4(2y-6)-8 | | -4=-4*-1 | | -8x+2y=5 | | 24a^3+3b^3= | | 4+2x-8x+10+11x=-1 | | -6x-18=33-9x | | -5y+6=-12+62 | | -5+2v=-1 | | 4/16=x/35 | | 3x+76=8x-14 | | 5(x-4)-2(x+5)=15 | | x^3-xy+y^3=1 | | x+3=2XA+7 | | 4q/7=1/5 | | 9(y+3)-5(2y-4)=47 | | 9x-116=-4x+105 | | 8-3(2-n)-17= |